Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/prs.0000000000007944
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Orbital Arterial Distribution Using Image Superimposition to Determine Safe Zones for Retrobulbar Injection and to Prevent Filler Complications

Abstract: nsufficient orbital volume-along with its various causes, including trauma and loss of the eye following enucleation or evisceration-is a challenging problem for craniofacial and oculoplastic surgeons. 1 This condition causes enophthalmos and deep upper eyelid sulcus, which is a significant determinant of the facial appearance. Also, the sunken and shallow fornix caused by insufficient orbital volume in anophthalmic socket syndrome cannot be completely resolved by simply increasing the size of the implanted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…We highly appreciate Dr. Sun and Dr. Long for their interest in and comments on our study. 1 We agree with their concern about the risk of filler injection within danger zones, such as the glabellar area of the face and the retrobulbar area. Although previous reports have suggested that retrobulbar filler injection is a relatively safe and tolerable procedure for orbital volume enhancement, concern remains about vascular complications such as orbital hemorrhage and arterial occlusion resulting in ophthalmoplegia, vision loss, and cerebrovascular infarction.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…We highly appreciate Dr. Sun and Dr. Long for their interest in and comments on our study. 1 We agree with their concern about the risk of filler injection within danger zones, such as the glabellar area of the face and the retrobulbar area. Although previous reports have suggested that retrobulbar filler injection is a relatively safe and tolerable procedure for orbital volume enhancement, concern remains about vascular complications such as orbital hemorrhage and arterial occlusion resulting in ophthalmoplegia, vision loss, and cerebrovascular infarction.…”
supporting
confidence: 72%
“…In our article, we suggested the safe direction for injection of fillers or other materials escaping arteries. 1 We have already reported on the depth of injection in the orbit with regard to eyeball protrusion and eyeball size. 6 In summary, we think that the safe guideline for retrobulbar injection was confirmed.…”
mentioning
confidence: 99%
“…We read with great interest the article entitled “Investigation of the Orbital Arterial Distribution Using Image Superimposition to Determine Safe Zones for Retrobulbar Injection and to Prevent Filler Complications,” 1 and we wish to congratulate the authors. A total of 27 Korean cadaveric orbital dissections were completed by the authors.…”
mentioning
confidence: 99%